64Cu-DOTATATE Uptake in a Pulmonary Hamartoma. (6th January 2023) - Song, Hong; Guja, Kip E.; Yang, Eric J.; Guo, Haiwei Henry
Abstract: DOTATATE PET/CT is frequently used to evaluate indeterminant pulmonary nodules suspected to be pulmonary carcinoid. We report an unexpected case of pulmonary hamartoma demonstrating 64 Cu-DOTATATE uptake in a 43-year-old woman with a slowly enlarging pulmonary nodule. Histopathological staining showed somatostatin receptor 2 expression on vascular endothelial cells and a proportion of cartilage and smooth muscle cells within the hamartoma.